trabajo social y erradicación de la violencia de género en la junta cantonal de protección de derechos, santa rosa, 2023. - Gallegos Ochoa, Erika Yelena; Tinitana Olives, Cecibel Del Cisne (Machala: Universidad Tecnica de Machala, 2024)
Gender violence is a global problem that primarily affects women and girls at different levels, such as sexual, physical, psychological, emotional and economic violence. In Ecuador, despite efforts to address this problem, significant challenges persist due to cultural and social norms that perpetuate gender inequality and discrimination. In the province of El Oro, the Cantonal Board for the Protection of Rights in Santa Rosa is dedicated to implementing the gender violence protection law, facing the lack of resources and inter-institutional coordination to eradicate gender violence. Social Work plays a fundamental role in the identification, prevention and care of gender violence. The research focuses on analyzing the role of Social Work in the eradication of gender violence against women in the Cantonal Board for the Protection of Rights in Santa Rosa in 2023. The aim is to investigate how cases of violence against women are addressed in this institution and to identify the challenges and barriers that Social Work faces in its work to eradicate gender violence. The intervention of Social Work in the face of gender violence seeks to be a facilitator in the care of victims, analyzing the causes and consequences of violence against women. The Cantonal Board for the Protection of Rights guarantees compliance with human rights and access to justice for victims of violence. In Ecuador, despite the public policies and laws created to combat gender violence, it continues to be a relevant problem that negatively affects the quality of life of women. The epistemological and philosophical foundation is based on human rights, the gender approach, theories of social change and ethical values ​​of Social Work. In Latin America, gender violence is a problem that has generated alerts and calls for its prevention and eradication, with the need for strategies that promote access to education, work and citizen participation for women. The proposed modification of the accompaniment modality in the Cantonal Board for the Protection of Rights seeks to optimize home visits and case management to improve the efficiency and effectiveness of interventions. The results of the intervention show a positive reception by the institution's professionals, who recognize its potential for successful implementation. It is crucial to note that, despite the theoretical acceptance and positive feedback obtained, the final results have not yet been validated, since the modification of the accompaniment modality for better care has not yet been fully implemented. The modification of the accompaniment modality represents a significant advance in the protection of rights, improving intervention procedures and allowing a more agile and effective response to the protection needs of victims of gender violence, although the proposal offers a compromising method to optimize the monitoring and protection of victims of gender violence. Chapter I: This section presents the theoretical part of the content, contextualization of the study, central problem, complementary problems, justification, general objective, specific objectives, epistemological foundation, theoretical framework, legal framework, methodological aspects and universe / sample. Chapter III: In this section To understand the circumstances and demands of the affected people, the organization of the diagnostic process is divided into three stages: planning, execution and evaluation. In addition, the diagnosis is made with techniques and instruments chosen to collect information. Chapter III: This section details the intervention plan that is carried out according to the identified problem. Based on the identification of these problems, a proposal was developed to improve the process, with its objectives, schedule and budget at hand. Chapter IV: In this final section of the work, the achievements of the results obtained from the intervention plan during the execution of the proposal in the institution are presented in a systematization, in addition to finishing the degree work, the recommendations and conclusions are mentioned.
La violencia de género hacia las mujeres constituye un fenómeno complejo y profundamente arraigado que impacta a la sociedad en múltiples dimensiones, manifestándose en formas de agresión sexual, física, psicológica, emocional y económica. En el contexto específico de la Junta Cantonal de Protección de Derechos del cantón Santa Rosa, desempeña un papel esencial en la implementación de legislaciones y acciones orientadas a la mitigación de esta problemática. Este estudio tiene como finalidad analizar y proponer mejoras en las estrategias de intervención y asistencia a las víctimas de violencia de género dentro de esta institución. Para recopilar y analizar los datos, se utilizará un enfoque mixto (cualitativo-cuantitativo). Para una comprensión más exhaustiva del problema, se emplearon diversas metodologías investigativas. Se llevó a cabo una entrevista con la trabajadora social de la Junta Cantonal de Protección de Derechos con el fin de obtener una perspectiva detallada sobre los procedimientos y mecanismos vigentes para el apoyo a las víctimas de violencia de género. Esta entrevista proporcionó información crucial sobre el funcionamiento interno de la Junta Cantonal y los desafíos operativos que enfrenta en su labor cotidiana. Con base en la identificación de estos problemas, se desarrolló una propuesta para mejorar el proceso de seguimiento y supervisión de las usuarias. Se propone la Implementación de modalidad hibrida (presencial y/o virtual) en caso excepcionales de seguimiento del equipo multidisciplinario de acompañamiento para las usuarias víctimas de violencia de género de la Junta Cantonal de Protección de Derechos, con el objetivo de asegurar un seguimiento más continuo y eficaz de sus casos. Esta modificación debería incluir la optimización de los procedimientos para garantizar que cada caso reciba la atención necesaria en el momento adecuado. Esta propuesta ahora ha recibido comentarios positivos por parte del equipo multidisciplinarios, que reconocen su potencial y están dispuestos aceptar la nueva modalidad de acompañamiento a las usuarias, reciben positivamente la propuesta por el equipo multidisciplinario de la Junta cantonal. Sin embargo, los resultados finales aún no pueden confirmarse ya que aún están pendientes la implementación completa y la evaluación de impacto. El Capítulo I: En este apartado se plantea la parte teórica del contenido, contextualización del estudio, problema central, problemas complementarios, justificación, objetivo general, objetivos especifico, fundamentación epistemológica, marco teórico, marco legal, aspectos metodológico y universo / muestra. El Capítulo III: En este apartado Para comprender las circunstancias y las demandas de las personas afectadas, la organización del proceso diagnóstico se divide en tres etapas: planificación, ejecución y evaluación. Además, se realiza el diagnostico con técnicas y instrumentos escogidos para recolectar información. El Capítulo III: En este apartado se detalla el plan de intervención que se realiza según la problemática identificada. Con base en la identificación de estos problemas, se desarrolló una propuesta para mejorar el proceso, con sus objetivos, cronograma y el presupuesto al cansado. El Capítulo IV: En este apartado final del trabajo, se presenta en una sistematización los logros de los resultados obtenidos del plan de intervención durante la ejecución de la propuesta en la institución, además también para finalizar el trabajo de titulación se mencionan las recomendaciones y conclusiones.
Keywords: VIOLENCIA DE GENERO; MUJERES; DERECHOS; TRABAJO SOCIAL